Microbiota of preterm infant develops over time along with the first teeth eruption - Zhang, Yu; Wu, Yi-Pei; Feng, Vivien; Cao, Gui-Zhi; Feng, Xi-Ping; Chen, Xi (Frontiers in Microbiology, 2022)
The temporal growth of the infant microbiome in the early years of life influences short- and long-term infant health. The aim of this longitudinal study was to investigate bacterial dynamics in the microbiome of preterm infants during tooth eruption. Saliva samples from normally delivered (n = 24) and preterm infants (n = 31) were collected 30 days after birth and after the eruption of two primary mandibular incisors. Based on Illumina MiSeq Sequencing of the 16S rRNA gene, the dynamic microbial changes of newborns at two-time points were investigated. Meanwhile, the Human Oral Microbiome Database was adopted for assigning taxonomy. Using alpha and beta diversity analyses, different shift patterns of microbiome structures in preterm and healthy participants and bacterial diversity over time were observed. In addition, the relative abundance and shifts trend, along with the two lower primary central incisors eruption, of core oral flora varies in full-term and preterm groups, including Gemella spp., Rothia mucilaginosa, Veillonella atypica, etc. Several microorganisms colonize later in the oral microbiome development of premature babies, such as Gemella spp. In addition to teeth eruption, the growth of the saliva microbiome in preterm infants could be influenced by breastfeeding durations and birth weight. In addition, this study provided insights into how the oral microbiota changes during tooth eruption in preterm infants and how the colonization of the oral cavity with bacteria in preterm infants differs significantly from that in full-term infants.